Does Percutaneous Left Atrial Appendage Closure Affect Left Atrial Performance? - Madeira,Marta (2018)
Abstract Background: Percutaneous left atrial appendage (LAA) occlusion may be an alternative therapy for atrial fibrillation (AF) patients with contraindication for anti-coagulation therapy. However, the influence of LAA occlusion on left atrial (LA) performance has not been studied. Objective: Our aim was to evaluate the influence of percutaneous LAA occlusion device on LA function by transthoracic echocardiography plus speckle-tracking echocardiography (STE). Methods: We included 16 patients undergoing percutaneous LAA closure with adequate echocardiographic window for the study of LA mechanics. Transthoracic echocardiography was performed before and after the procedure. LA volumes were calculated using the biplane method, and LA mechanics were assessed using STE. The analysis focused on the LA reservoir phase strain and strain rate. Results: Seventy-five percent of patients had permanent atrial fibrillation. Embolic and bleeding risk scores used were CHA2DS2-VASc [median of 4-5] and HAS-BLED [median of 2-3]. Major bleeding (62%) was the most common indication for the procedure. Percutaneous LAA closure was performed successfully in all patients, without major complications. No differences were found in maximum LA volume (44 ± 11 vs. 46 ± 13 mL/m2; p = 0.54), minimum LA volume (32 ± 8 vs. 37 ± 14 mL/m2; p = 0.09) or LA emptying fraction (26 ± 17 vs. 21 ± 14%; p = 0.33) before and after the procedure. Similarly, no differences were noted in left atrial strain (13.7 ± 11.1 vs. 13.0 ± 8.8%; p = 0.63) or strain rate (1.06 ± 0.26 vs. 1.13 ± 0.34 s-1; p = 0.38) in the reservoir phase. Conclusions: Our data suggest that percutaneous LAA closure does not affect LA reservoir function.